(untitled) (Journal of Ideas in Health, 2024)
Background: This study seeks to assess gender differences in the severity of COVID-19 infection, which have been noted in different regions during the early stages of the pandemic. Methods: A cross-sectional study conducted at Baquba Teaching Hospital in Diyala, Iraq, from October 1st to December 31st, 2020, included 132 confirmed COVID-19 patients. These patients underwent a comprehensive set of routine laboratory tests, including complete blood count, blood biochemistry, and D-dimer assessment. Statistical analysis was carried out using SPSS-20, with significance set at p < 0.05. Results: The study included patients with a mean age of 45.61 (±11.32) years, predominantly male (63.0%), residing in urban areas (57.6%), and presenting with comorbidities (78.8%). All patients exhibited positive results on CT scans (100%) and CRP tests (100%). However, PCR testing confirmed COVID-19 infection in 87.2% of cases, with 12.8% testing negative. Among males, there was a significant increase in IL-6 and IL-10 levels (42.57 ± 7.64 pg/ml and 255.27 ± 21.03 pg/ml) compared to females (16.43 ± 4.19 pg/ml and 187.48 ± 20.35 pg/ml), with p-values <0.001 and 0.003, respectively. Conversely, there was no significant difference in IFN-ɣ levels between males (165.73 ± 16.54 pg/ml) and females (176.12 ± 17.10 pg/ml), with a p-value of 0.105. However, lymphocyte levels were significantly lower in males (4.79 ± 0.85%) compared to females (14.01 ± 1.36%), with a p-value <0.001. Conclusion: Overall, COVID-19 affects males more severely than females, with males showing weaker immune responses and higher levels of inflammatory cytokines like IL-6 and IL-10. While IFN-ɣ levels do not differ significantly between genders, males have lower lymphocyte counts compared to females.